A portable RGB color sensor for detecting free fatty acid (FFA) in palm oil samples - Nunumvong, Vakin; Teeparuksapun, Kosin; Prasongchan, Nicha; Phonchai, Apichai (Asia-Pacific Journal of Science and Technology, 2024)
A colorimetric sensor based on red, green, blue (RGB) measurement using an OV2640 camera module and ESP32 microcontroller was developed for measuring free fatty acid (FFA) in crude palm oil samples. The proposed method is based on measuring the color of liquid samples and convert it to RGB and Grayscale intensity. The RGB sensor’s performance was evaluated for application in analysing FFA in crude palm oil samples. The FFA analysis was based on the application of the limiting reagent concept in an acid-base (palmitic acid-Na2CO3) reaction with phenolphthalein as an indicator. The RGB sensor could detect FFA with a linear relationship in the range of 0.0 - 0.1 % w/w and the linear regression equation was y = 1,125x - 2.8056, r = 0.9923, with limit of detection (LOD) and limit of quantification (LOQ) having values of 0.017 and 0.057 % w/w, respectively. The analysis of FFA in crude palm oil samples showed good agreement with results obtained from the proposed RGB sensor and the titration method (AOCS; Ca5a-40). This simple, rapid, and economical analysis method for assessing FFA holds promise for application in the quality control of crude palm oil samples.